Basic technique of ERCP and advanced technique for difficult selective biliary cannulation - Sugiyama, Harutoshi; Tsuyuguchi, Toshio; Yokosuka, Osamu; Nishikawa, Takao; Sakai, Yuji (Tando, 2014)
Selective cannulation to the bile duct, that is, biliary cannulation is the basic for diagnosis and treatment technique of a biliary disease which needs ERCP. There are patients with difficulty in cannulation to the bile duct at a certain ratio, even if any excellent surgeon performs. Therefore, various attempts have been conducted to improve the success rate. This paper explains how procedural accidents are prevented and how the success rate of biliary cannulation is improved based on our cases as well as the literature discussion.